2021
DOI: 10.4258/hir.2021.27.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Korean Electronic Data Interchange Vocabulary into Observational Medical Outcomes Partnership Vocabulary

Abstract: Objectives: We incorporated the Korean Electronic Data Interchange (EDI) vocabulary into Observational Medical Outcomes Partnership (OMOP) vocabulary using a semi-automated process. The goal of this study was to improve the Korean EDI as a standard medical ontology in Korea. Methods: We incorporated the EDI vocabulary into OMOP vocabulary through four main steps. First, we improved the current classification of EDI domains and separated medical services into procedures and measurements. Second, each EDI concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In the previous study, it was found that the integration of the EDI vocabulary into the OMOP vocabulary facilitates the standardization of EDI vocabulary per se. 6) …”
Section: Standardization Data Quality and Risk Of Re-identification O...mentioning
confidence: 99%
“…In the previous study, it was found that the integration of the EDI vocabulary into the OMOP vocabulary facilitates the standardization of EDI vocabulary per se. 6) …”
Section: Standardization Data Quality and Risk Of Re-identification O...mentioning
confidence: 99%
“…It has advantages as a data source in that it is structured and domestic standardized. However, EDI term has not been acknowledged as a standard vocabulary in the way that the Current Procedural Terminology, fourth edition has in the United States because its quality has never been audited 19 . Instead, there were several attempts to map the EDI term to SNOMED-CT 20 – 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite many useful applications offered by concept normalizations, such as aligning data sources between different institutions, these opportunities are limited when such concept ontologies in non-English are limited or the local institution's text EHR is especially noisy. For example, despite many Korean medical communities' huge interest in mapping their local EHR to standardized concepts [28,[67][68][69][70], the Korean-translated version of LOINC was only recently released in 2022 [71]. Therefore, these preliminary key concepts generated from XLM-RoBERTa suggest an exciting potential role of transformerbased language models in building or expanding non-English text resources at the individual medical institution level.…”
Section: Lif T(w) =mentioning
confidence: 99%